Pentaradial eukaryote suggests expansion of suspension feeding in White Sea-aged Ediacaran communities - Cracknell, K; García-Bellido, DC; Gehling, JG; Ankor, MJ; Darroch, SAF; Rahman, I (Springer Nature, 2021)
Suspension feeding is a key ecological strategy in modern oceans that provides a link between pelagic and benthic systems. Establishing when suspension feeding first became widespread is thus a crucial research area in ecology and evolution, with implications for understanding the origins of the modern marine biosphere. Here, we use three-dimensional modelling and computational fluid dynamics to establish the feeding mode of the enigmatic Ediacaran pentaradial eukaryote Arkarua. Through comparisons with two Cambrian echinoderms, Cambraster and Stromatocystites, we show that flow patterns around Arkarua strongly support its interpretation as a passive suspension feeder. Arkarua is added to the growing number of Ediacaran benthic suspension feeders, suggesting that the energy link between pelagic and benthic ecosystems was likely expanding in the White Sea assemblage (~ 558–550 Ma). The advent of widespread suspension feeding could therefore have played an important role in the subsequent waves of ecological innovation and escalation that culminated with the Cambrian explosion.